Human Cardiac-Derived Stem/Progenitor Cells Fine-Tune Monocyte-Derived Descendants Activities toward Cardiac Repair - Dam, Noémie; Hocine, Hocine Rachid; Palacios, Itziar; DelaRosa, Olga; Menta, Ramón; Charron, Dominique; Bensussan, Armand; El Costa, Hicham; Jabrane-Ferrat, Nabila; Dalemans, Wilfried; Lombardo, Eleuterio; Al-Daccak, Reem (Frontiers in Immunology, 2017)
Cardiac repair following MI relies on a finely regulated immune response involving sequential recruitment of monocytes to the injured tissue. Monocyte-derived cells are also critical for tissue homeostasis and healing process. Our previous findings demonstrated the interaction of T and natural killer cells with allogeneic human cardiac-derived stem/progenitor cells (hCPC) and suggested their beneficial effect in the context of cardiac repair. Therefore, we investigated here whether monocytes and their descendants could be also modulated by allogeneic hCPC towards a repair/anti-inflammatory phenotype. Through experimental in vitro assays, we assessed the impact of allogeneic hCPC on the recruitment, functions and differentiation of monocytes. We found that allogeneic hCPC at steady state or under inflammatory conditions can incite CCL-2/CCR2-dependent recruitment of circulating CD14+CD16- monocytes and fine-tune their activation toward an anti-inflammatory profile. Allogeneic hCPC also promoted CD14+CD16- monocyte polarization into anti-inflammatory/immune-regulatory macrophages with high phagocytic capacity and IL10 secretion. Moreover, hCPC bended the differentiation of CD14+CD16- monocytes to dendritic cells toward anti-inflammatory macrophage-like features and impaired their antigen-presenting function in favor of immune-modulation. Collectively, our results demonstrate that allogeneic hCPC could reshape monocytes, macrophages as well as dendritic cells responses by favoring their anti-inflammatory/tolerogenic activation/polarization. Thereby, therapeutic allogeneic hCPC might also contribute to post-infarct myocardial healing by modeling the activities of monocytes and their derived descendants.